2019
DOI: 10.3389/fonc.2019.01179
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nasopharyngeal Cancer in Young Patients Aged ≤ 30 Years

Abstract: Purpose: This study assessed the prognosis of young patients with nasopharyngeal cancer (NPC), both domestic and foreign, using data from the Surveillance, Epidemiology and End Results (SEER) database, a population-based database, and departmental records.Methods: Patients diagnosed with NPC from 2004 to 2016 in the SEER database were reviewed. Young patients aged ≤30 years when diagnosed, were compared with older patients. The medical records of patients with NPC aged ≤30 years in our own department were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
2
13
0
4
Order By: Relevance
“…NPC patients in Taiwan were characterized by more males, and 80% of them were under 60 years old in another study ( Song et al, 2019 ). The 5-years overall mortality for NPC patients was approximately 30% in our study, which is in agreement with previous studies ( Ji et al, 2019 ; Zhu et al, 2019 ). We found that the 5-years overall mortality for patients with NPC was about 25% when patients used CHM.…”
Section: Discussionsupporting
confidence: 93%
“…NPC patients in Taiwan were characterized by more males, and 80% of them were under 60 years old in another study ( Song et al, 2019 ). The 5-years overall mortality for NPC patients was approximately 30% in our study, which is in agreement with previous studies ( Ji et al, 2019 ; Zhu et al, 2019 ). We found that the 5-years overall mortality for patients with NPC was about 25% when patients used CHM.…”
Section: Discussionsupporting
confidence: 93%
“…NPCs are primary tumors in adult patients with a peak prevalence between the ages of 40 and 60, although this type of cancer can also occur in children 10,11) . The predominant male-to-female ratio is about 3/1, irrespec- Other carcinoma (n = 10) 0 0 tive of geographic location 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with patients with NPC aged >30 years, those aged ≤ 30 years have been reported to have a more advanced stage and poor pathologic differentiation in initial diagnosis but more favorable outcomes, possibly due to tolerance to more aggressive chemotherapy and better family and financial support [7,34]. After intensity modulation radiation therapy (IMRT) treatment, juvenile patients exhibited better outcomes but more severe cytotoxicity than did adults [35].…”
Section: Egf-egfr Pathway Activation In the Young Age Groupmentioning
confidence: 99%
“…Individual genetic susceptibility, Epstein-Barr virus (EBV) infection, and dietary or chemical carcinogens are the main etiological factors contributing to NPC pathogenesis [2][3][4][5]. The majority of patients with NPC are aged between 40 and 60 years, and NPC has been rarely diagnosed in patients aged below 30 years and above 70 years [6,7]. Adolescents and young adults with cancer are likely to have poor outcomes because of the molecularly distinct tumor signature, predisposition to genetic mutations, and severe clinical manifestations [8,9].…”
Section: Introductionmentioning
confidence: 99%